2010
DOI: 10.1371/journal.ppat.1000925
|View full text |Cite
|
Sign up to set email alerts
|

The SOCS-Box of HIV-1 Vif Interacts with ElonginBC by Induced-Folding to Recruit Its Cul5-Containing Ubiquitin Ligase Complex

Abstract: The HIV-1 viral infectivity factor (Vif) protein recruits an E3 ubiquitin ligase complex, comprising the cellular proteins elongin B and C (EloBC), cullin 5 (Cul5) and RING-box 2 (Rbx2), to the anti-viral proteins APOBEC3G (A3G) and APOBEC3F (A3F) and induces their polyubiquitination and proteasomal degradation. In this study, we used purified proteins and direct in vitro binding assays, isothermal titration calorimetry and NMR spectroscopy to describe the molecular mechanism for assembly of the Vif-EloBC tern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
101
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(110 citation statements)
references
References 48 publications
6
101
0
3
Order By: Relevance
“…Vif acts as a substrate receptor for a Cullin5-Ring E3 (Cul5-E3) ubiquitin ligase complex, which can induce polyubiquitination (poly-Ub) and degradation of A3 enzymes (8,9). This process is mediated by Vif binding to host Cullin5 and the elongin B/C heterodimer (EloB/C) through specific motifs in Vif that mimic human SOCS2 (10)(11)(12)(13)(14). Vif also binds with the transcription cofactor CBF␤ for thermodynamic stability (15,16).…”
mentioning
confidence: 99%
“…Vif acts as a substrate receptor for a Cullin5-Ring E3 (Cul5-E3) ubiquitin ligase complex, which can induce polyubiquitination (poly-Ub) and degradation of A3 enzymes (8,9). This process is mediated by Vif binding to host Cullin5 and the elongin B/C heterodimer (EloB/C) through specific motifs in Vif that mimic human SOCS2 (10)(11)(12)(13)(14). Vif also binds with the transcription cofactor CBF␤ for thermodynamic stability (15,16).…”
mentioning
confidence: 99%
“…Concerning Vif, the oligomerization sequence has been mapped between residues 151 and 164 in the C-terminal domain and more specifically to the 161 PPLP 164 motif (37,38,45). The PPLP motif was found to be required for the assembly of an active E3 ubiquitin ligase complex (43,44), and mutation of this sequence or the use of antagonist peptides has been shown to result in an important loss of viral infectivity (57), one of the reasons being an increased incorporation of A3G into viral particles as a consequence of the inhibition of its degradation (37,40,41,57).…”
Section: Discussionmentioning
confidence: 99%
“…This short domain was found to be crucial for Vif function and viral infectivity (37)(38)(39). Moreover, it can interact with A3G (40,41), cullin 5 (42), and the HIV-1 reverse transcriptase (35), and it was also observed that an intact PPLP motif is required for interaction between Vif and elongin B (43,44). Considering the involvement of the PPLP motif in Vif oligomerization, it is conceivable that all of these binding functions could be linked to the multimerization state of Vif.…”
mentioning
confidence: 99%
“…Long-range electrostatic interactions were calculated using the particle mesh Ewald (PME) method. The Berendsen thermostat was applied using a coupling time of 0.1 ps to maintain the system at a constant temperature of 300 K, and the pressure was also maintained by coupling to a reference pressure of 10 5 Pa by a Berendsen thermostat. The complex simulation began with 5,000-step energy minimization with conjugate gradient algorithm.…”
Section: Hiv-1 Infection Of Human T Cell Linesmentioning
confidence: 99%